স্বাধীনতা সংগ্রামে ভারতের জাতীয় কংগ্রেস, ১৮৮৫-১৯৪৭ - ত্রিপাঠী, অমলেশ, ১৯২১- (কলকাতা : আনন্দ পাবলিশার্স, 2008)
This volume presents an analytical history of India's struggle for freedom and the role played in it by the Indian National Congress. Drawing on statistical analysis and exhaustive research, it provides a comprehensive account of the Independence movement, encompassing events such as the extremist-moderate split in the Congress, Morley-Minto reforms, Round Table Conferences, the Quit India Movement, and the Partition.
First published in Bengali as Swadhinata Sangrame Bharater Jatiya Congress (1885-1947) in 1990.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ৫৫৯- [৫৬৭]) ও নির্ঘণ্ট অন্তর্ভুক্ত।
Translated from the Bengali.
Keywords: Indian National Congress -- History; Nationalism -- India -- History; Political science; India -- Politics and government -- 1765-1947.